2021
DOI: 10.1093/hmg/ddab301
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of Kv8.2 loss on rod and cone signaling and degeneration

Abstract: Heteromeric Kv2.1/Kv8.2 channels are voltage-gated potassium channels localized to the photoreceptor inner segment. They carry IKx, which is largely responsible for setting the photoreceptor resting membrane potential. Mutations in Kv8.2 result in childhood-onset Cone Dystrophy with Supernormal Rod Response (CDSRR). We generated a Kv8.2 knockout (KO) mouse and examined retinal signaling and photoreceptor degeneration to gain deeper insight into the complex phenotypes of this disease. Using electroretinograms w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Consistent with our current findings, Kv2.1 and Kv8.2 were shown earlier to be highly expressed in photoreceptor IS, but absent or poorly expressed in other retinal layers [ 26 , 27 ]. This agrees with our immunohistochemical localization of retinoschisin and the retinal Na/K-ATPase revealing a strong enrichment at the IS of the photoreceptors [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our current findings, Kv2.1 and Kv8.2 were shown earlier to be highly expressed in photoreceptor IS, but absent or poorly expressed in other retinal layers [ 26 , 27 ]. This agrees with our immunohistochemical localization of retinoschisin and the retinal Na/K-ATPase revealing a strong enrichment at the IS of the photoreceptors [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similar to retinoschisin-deficient mice [ 56 58 ], recent studies of Jiang and colleagues as well as of Inamdar and colleagues reported that Kv8.2 knockout mice reveal a significantly higher apoptotic cell count, a thinner retina, and increased microglia occurrence in the subretinal space [ 27 , 28 ]. Interestingly, the localization of Kv2.1 was found to be unaffected in Kv8.2 knockout mice [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our current ndings, Kv2.1 and Kv8.2 were shown earlier to be highly expressed in photoreceptor IS, but absent or poorly expressed in other retinal layers [24,31]. This agrees with our immunohistochemical localization of retinoschisin and the retinal Na/K-ATPase revealing a strong enrichment at the IS of the photoreceptors [6].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to retinoschisin-de cient mice [36,46,47], recent studies of Jiang and colleagues as well as of Inamdar and colleagues showed that Kv8.2 knockout mice reveal a signi cantly higher apoptotic cell count, a thinner retina, and increased microglia occurrence in the subretinal space [31,48]. Interestingly, the localization of Kv2.1 was found to be unaffected in Kv8.2 knockout mice [48].…”
Section: Discussionmentioning
confidence: 97%
“…The waveform below 2 Hz was not sinusoidal suggesting the possibility of nonlinear responses at low frequencies and strikingly the waveform and phase of the response was very different between controls and Rod-HCN1 KO. To take that into account we previously characterized the sinusoidal flicker response to low frequency waveforms as being composed of "b-wave-like" and "c-wave-like" components with a large recovery phase between the two (Inamdar et al, 2021). Applying that characterization here, the altered response waveform in the HCN1-Rod KO mice appeared consistent with these two components merging, as would be expected from a prolonged b-wave.…”
Section: Generation Of Hcn1-rod Ko Micementioning
confidence: 76%